Open sequential, open staged, and laparoscopic-assisted approaches - Shanmugam, Subbiah; Bharath, Radha Siva (International Journal of Research in Orthopaedics, 2023)
Background: This retrospective study evaluates sacrectomy techniques and associated outcomes in 32 patients at our department. Sacrectomy, challenging due to complex anatomy and vascularization, has evolved from open single-stage abdomino-sacral to a staged approach and laparoscopic-assisted methods. Methods: We examined total, subtotal, and partial sacrectomies, transitioning from a single-stage to a staged procedure (with a 1-2 day gap) and finally to laparoscopic-assisted sacrectomy. We focused on postoperative morbidity. Results: Results show 14 partial, 8 subtotal, 8 total, and 2 laparoscopic-assisted partial sacrectomies. Giant cell tumors and chordomas were common. The staged approach was used in 16 patients, the sequential in 12, and laparoscopic in 2. The latter, despite longer surgery times, resulted in less blood loss, shorter hospital stays, less pain, and faster recovery. Wound dehiscence was the main complication, typically managed conservatively or with skin grafts. One case required a gluteal flap. Bowel and bladder dysfunctions, mostly following total and subtotal sacrectomies, improved with conservative management. The staged approach showed reduced morbidity compared to the sequential. Conclusions: In conclusion, sacrectomy has become less morbid due to improved anatomical understanding, surgical advancements, and rehabilitation. Staged sacrectomy reduces peri-operative morbidity versus the sequential method. Laparoscopic-assisted sacrectomy, promising reduced blood loss, pain, and hospitalization, requires careful patient selection.